1998
DOI: 10.1161/01.res.83.6.661
|View full text |Cite
|
Sign up to set email alerts
|

Caldesmon Inhibits Active Crossbridges in Unstimulated Vascular Smooth Muscle

Abstract: Caldesmon is a thin-filament-associated protein believed to be important in the regulation of smooth muscle contraction, although the precise mechanism is unknown. We used antisense oligodeoxynucleotides to produce intact swine carotid smooth muscle tissue deficient in h-caldesmon. Caldesmon content was decreased by 78% after 7 days in culture with antisense oligodeoxynucleotides but was unchanged in tissues in the presence of sense oligodeoxynucleotides or vehicle. Antisense oligodeoxynucleotides produced a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
74
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 32 publications
7
74
1
Order By: Relevance
“…It has been reported that extraction of caldesmon from a permeabilized smooth muscle preparation increased the Ca 2ϩ sensitivity of force development (20) and, conversely, that addition of caldesmon or a C-terminal fragment to permeabilized chicken gizzard fibers inhibited contraction (21)(22). It has also been reported recently that, in arterial strips made caldesmon-deficient by the use of antisense oligodeoxynucleotides, increased basal crossbridge cycling rates are inhibited by the addition of caldesmon (23).…”
Section: Phosphorylation Of Sermentioning
confidence: 81%
“…It has been reported that extraction of caldesmon from a permeabilized smooth muscle preparation increased the Ca 2ϩ sensitivity of force development (20) and, conversely, that addition of caldesmon or a C-terminal fragment to permeabilized chicken gizzard fibers inhibited contraction (21)(22). It has also been reported recently that, in arterial strips made caldesmon-deficient by the use of antisense oligodeoxynucleotides, increased basal crossbridge cycling rates are inhibited by the addition of caldesmon (23).…”
Section: Phosphorylation Of Sermentioning
confidence: 81%
“…Bladder strips were also processed for the determination of myosin-to-actin ratios with minor modifications of techniques previously reported (5). Briefly, aliquots of the homogenized tissues were subjected to SDS-PAGE.…”
Section: Methodsmentioning
confidence: 99%
“…In an in vitro reconstituted system, caldesmon inhibits actomyosin ATPase activity. In vivo studies using smooth muscle cells have supported the inhibitory function of caldesmon in smooth muscle contraction (Katsuyama et al, 1992;Pfitzer et al, 1993;Huber, 1997;Earley et al, 1998;Burton and Marston, 1999). A recent report has implied a similar function for caldesmon in nonmuscle cells (Helfman et al, 1999).…”
Section: Introductionmentioning
confidence: 96%